Induksi Multiplikasi Tunas Anthurium Wave of Love (Anthurium plowmanii) secara In Vitro - Nurul Khumaida; Riyanti Catrina H S; Dewi Sukma (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2012)
ABSTRACTAnthurium plowmanii is one of leafy ornamental plants known as anthurium Wave of Love. This plant has a unique characteristic including wave along the leaf side. The aim of this research was to analyze the effect of basic media composition and BAP concentration on in vitro shoot multiplication of Anthurium. Sterile young shoot of Anthurium was used as explant. Three basic media composition including MS, ½MS, and Hyponex and its combination with 0.00 µM BAP, 2.22 µM, 6.66 µM, and 13.32 µM were used as treatments. The result showed that the best medium to induce shoot multiplication were MS + 6.66 µM BAP and ½MS + 13.32 µM BAP which produced 10.4 and 10.3 shoots respectively, higher than other treatments. Medium MS + BAP 13.32 µM decreased the time of shoot initiation. This medium was useful for shoot multiplication of Anthurium plowmanii.Key words: shoot, multiplication, BAP, MS, Hyponex medium, Anthurium ‘Wave of Love’ABSTRAKAnthurium plowmanii adalah tanaman hias daun yang dikenal dengan nama ‘Gelombang Cinta’. Tanaman ini memiliki karakteristik unik, yakni gelombang spanjang tepi daun. Tujuan dari penelitian ini adalah menganalisa pengaruh dari komposisi media dan konsentrasi BAP terhadap multiplikasi tunas Anthurium secara in vitro. Eksplan yang digunakan adalah tunas Anthurium yang sudah disterilisasi. Tiga media dasar yang digunakan meliputi MS, ½ MS, dan Hyponex dan dikombinasikan dengan BAP sebesar 0.00 µM, 2.22 µM, 6.66µM, dan 13.32 µM sebagai perlakuan. Hasil menunjukkan bahwa media terbaik untuk multiplikasi tunas adalah MS + 6.66 µM BAP and ½MS + 13.32 µM BAP yang masing-masing menghasilkan 10.4 dan 10.3 tunas. Hasil tersebut lebih tinggi dibandingkan dengan perlakuan yang lain. Media MS + 13.32 µM BAP mampu mengurangi waktu inisiasi tunas. Media ini dapat berguna untuk multiplikasi tunas Anthurium plowmanii.Kata kunci: tunas, multiplikasi, BAP, MS, Hyponex, Anthurium ‘Gelombang Cinta’